Teachers’ perceptions of the roleplaying technique in teaching English speaking skills to non-English major students - An Truong Le (Ho Chi Minh City Open University Journal of Science - Social Sciences)
Roleplaying is considered a prominent teaching technique for teaching English speaking skills. However, little has been known about how teachers perceive its benefits, challenges, and learning outcomes when applying this technique to teaching English-speaking skills to predominantly non-English-major students. The case study, employing a mixed-method design, was conducted at Ho Chi Minh City Open University (HCMC OU). There were ten participants for quantitative data collected via questionnaire and 02 interviewees for semi-structured interviews to collect qualitative data. The SPSS version 20.0 was used to analyze data. The findings revealed that the participants perceived that the roleplaying technique significantly impacted students’ English confidence. However, the participants held neutrality regarding improving pronunciation and grammatical accuracy when teachers apply roleplaying techniques in teaching English speaking skills. The researcher draws some pedagogical implications and recommendations for future research based on the findings.